2022
DOI: 10.3390/healthcare10030480
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Convalescent COVID-19 Patients Undergoing Multidisciplinary Rehabilitation: The Association with the Clinical and Functional Status

Abstract: Background. Cognitive impairment has been reported in the aftermath of severe acute respiratory syndrome due to coronavirus 2 (SARS-CoV-2) infection. We investigated the possible association between cognitive impairment and the main clinical and functional status variables in a cohort of convalescent COVID-19 patients without premorbid diseases potentially affecting cognition. Methods. We consecutively screened for inclusion of convalescent COVID-19 patients referring to a post-acute care facility for pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
3
0
3
Order By: Relevance
“…As the presence of depression is linked to cognitive impairments, and a higher frequency of cognitive symptoms not always confirmed by the objective assessment ( 30 ), a subanalysis was conducted, excluding patients with depression.…”
Section: Methodsmentioning
confidence: 99%
“…As the presence of depression is linked to cognitive impairments, and a higher frequency of cognitive symptoms not always confirmed by the objective assessment ( 30 ), a subanalysis was conducted, excluding patients with depression.…”
Section: Methodsmentioning
confidence: 99%
“…We found that depression is widespread in patients have survived COVID-19, especially in women, and often co-exists with fatigue, dyspnea, and cognitive dysfunction, affecting patients’ quality of life [62, 63]. Therefore, psychological support and psychiatric intervention should be considered during the process of cardiac rehabilitation (Fig.…”
Section: Long-covid and Its Cardiovascular Sequelaementioning
confidence: 99%
“…Кроме того, пациенты с RCE имели значительно более высокие показатели тревожности, а также, как правило, демонстрировали более низкие показатели по опроснику EuroQol-5D (EQ-5D, Европейский опросник оценки качества жизни). Обращает внимание, что пациенты группы RCE чаще демонстрировали изменение циркадного ритма артериального давления (АД) (non-dipper), что подтверждает связь между когнитивными нарушениями и изменением циркадного ритма АД [29].…”
Section: когнитивные нарушения в постковидном периодеunclassified
“…Учитывая, что артериальная гипертензия является наиболее часто встречающейся патологией в структуре коморбидности НКВИ и имеет взаимосвязи с когнитивным статусом, нестабильное АД может играть важную роль в развитии когнитивных нарушений после COVID-19 [29].…”
Section: коморбидность когнитивный статус и постковидный синдромunclassified